Development Of Putu Bendera Promotional Media - Saputra, Wisnu Edi; Yulastri, Asmar; Fridayati, Lucy; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research was motivated by the absence of putu bendera promotional media in the form of making putu bendera advertising videos. The purpose of development in this study is to develop putu bendera promotional media in the form of putu bendera advertising videos so that putu bendera is better known to the wider community.This type of research is development research with the development model used is Planning, Production, and Evaluation (PPE). The trials in this study consist of 3, namely validity tests, practicality tests and effectiveness tests. While the data analysis technique used is a descriptive data analysis technique, namely by describing the validity, practicality, and effectiveness of using putu bendera ad videos.The results of this development conclude as follows; (1) Expert validation is declared very valid with an average value categorized as very valid (2) The practicality of the putu bendera ad video based on the practicality test on the putu bendera maker is declared very practical (3) The effectiveness of the putu bendera ad video based on the effectiveness test to the community in Barus District with the effective category. The conclusion of this study is that this putu bendera advertising video is valid, practical, and effective to increase public attraction to putu flag.